The ghost that haunted itself : the gruesome ghoul of edinburgh's greyfriars graveyard - Henderson, Jan-Andrew (Edinburgh : Mainstream Publishing, 2001)
Greyfrair's Cemetery in Edinburgh has a centuries old reputation for being haunted. Homes next to the graveyard wall became plagued by crockery smashing, objects moving and unidentified laughter. The section of Greyfriars where the attacks occurred is now chained shut.